If it's not what You are looking for type in the equation solver your own equation and let us solve it.
18=14+(4x-14)
We move all terms to the left:
18-(14+(4x-14))=0
We calculate terms in parentheses: -(14+(4x-14)), so:We move all terms containing x to the left, all other terms to the right
14+(4x-14)
determiningTheFunctionDomain (4x-14)+14
We get rid of parentheses
4x-14+14
We add all the numbers together, and all the variables
4x
Back to the equation:
-(4x)
-4x=-18
x=-18/-4
x=4+1/2
| 54.6=8.4x | | 10b=100000 | | 5x+12=67* | | 4^2-n=1/2048 | | 41=6y-4 | | 3×+2y=84 | | 5x-7=8(-5x+16) | | 88+54+x=180 | | 7+3x=5+-15 | | 8-7k=7k+10 | | 5x-7=-40x+128 | | 3x−324=x−433x−324=x−43 | | 3x−3/24=x−4/33x−324=x−43 | | 80=8a+184 | | 12-3n=6-2n | | 14p–6=9p+34 | | -2x+4=42 | | -2(4x-11)=-42 | | 6(-x-2)=-3x | | 2(x=7)-10 | | 12+3v=4v | | 99u-20+1.5u=8.25 | | -14.7=-2.2+u/5 | | 2x-3+2x+5+4x=50 | | 8=7-2y | | 2(3x+5)+5x=5(2x+3 | | 20m=45 | | 2x+1+2x+3+2x+5+2x+7=96 | | 10=6c=4 | | 2x+1+2x+1+2x+1+2x+1=96 | | 4.2x+1=96 | | 3(m-1)=5(m+2) |